Greeting Words in Kerincinese Found in Semerap and Pulau Tengah Dialect - Saputra, M. Robes; Jufrizal, Jufrizal (English Language and Literature, 2024)
This research aimed at finding the greeting words in Kerincinese found in Semerap and Pulau Tengah dialect and the similarities and differences of Kerincinese greeting words found in Semerap and Pulau Tengah dialect. The type of this research was descriptive qualitative method. The data were Kerincinese greeting words used by the informants. The informants of this research were Semerap and Pulau Tengah native speakers. The researcher found 95 greeting words found in Semerap and Pulau Tengah dialect. The researcher found four types of Kerincinese greeting words in Semerap dialect. They were kinship, customary, religious, and pronouns. Meanwhile, there were four types of Kerincinese greeting words found in Pulau Tengah dialect. They were kinship, customary, religious, and pronouns. The affixation in the Kerinci language especially in Semerap and Pulau Tengah dialect become the main reasons the greeting words in these two villages are different.